Konsep Wahyu dan Kenabian serta Implikasinya terhadap Pandangan Dunia Islam - Linggawijaya, Hamzah; Rasyid, Faiz; Permatasari, Indah Gilang; Sumiran, Sumiran (Lembaga Yasin AlSys, 2026)
This study aims to analyze in an integrated manner the concepts of wahyu (al-wahy) (divine revelation) and nubuwwah (prophethood) and their implications for shaping the Islamic worldview. The main problem addressed is the lack of an integrated analysis of the authority of the text (wahyu) and the figure (nubuwwah) in formulating a comprehensive structure of the Islamic worldview. The specific objective is to define the absolute authority of both and to examine their impact on the metaphysical, epistemological, and axiological dimensions. The study employs a qualitative method with a library research design and conceptual analysis. The findings show that wahyu constitutes absolute truth content, while nubuwwah functions as a preserved and final channel of transmission. The unity of the two fundamentally shapes an Islamic worldview that is centered on tauhid (metaphysical implication), places wahyu in the highest position as the source of knowledge (epistemological implication), and establishes absolute standards of morality (axiological implication. The study concludes that wahyu and nubuwwah are integral and anti-secular foundations. The implication is that the Islamic worldview must be grounded exclusively in the authentic text and its executor, while rejecting forms of rationalism or materialism that contradict the sharia.